Effects of warming and drought stress on the growth characteristics, photosynthetic-transpiration rates, and yield of winter wheat - Li, Qian; Gao, Yang; Mounkaila Hamani, Abdoul Kader; Wang, Guangshuai; Liu, Junming; Fu, Yuanyuan; Wang, Xingpeng (International Journal of Agricultural and Biological Engineering, 2024)
Climate change has limited crop productivity worldwide. Understanding crop response to global climate changes is vital to maintaining agricultural sustainable development. A two-year experiment was conducted to investigate the effects of warming and drought on crop growth and winter wheat yield production. The results showed that both warming and drought shortened the crop growth period, reduced the leaf area index, and increased winter wheat biomass accumulation. Under sufficient water supply conditions, warming would increase photosynthetic and transpiration rates and water use efficiency, while under water deficit conditions, the opposite was observed. Under warming conditions, the grain yield of the water deficit treatment was 8.9% lower than that of the sufficient water supply treatment. Under non-warming conditions, the grain yield of water deficit treatment was 12.4% lower than that of the sufficient water supply. Under the conditions of water-sufficient supply, the grain yield of the warming treatment was 4.4% lower than that of the non-warming treatment, and under the conditions of water deficit, the grain yield of the warming treatment was 1.3% lower than that of the non-warming treatment. Warming tends to decrease wheat growth and grain yield, but sufficient water supply could improve winter wheat’s water use efficiency and reduce the warming limitation on wheat production. Keywords: winter wheat, warming, leaf area index, photosynthetic rate, yield, biomass DOI: 10.25165/j.ijabe.20241703.8225 Citation: Li Q, Gao Y, Hamani A K M, Wang G S, Liu J M, Fu Y Y, et al. Effects of warming and drought stress on the growth characteristics, photosynthetic-transpiration rates, and yield of winter wheat. Int J Agric & Biol Eng, 2024; 17(3): 121-129.